A study on the characteristics of 1H NMR spectra and evaluation of the sensitivity of an electromagnetic induction system to differences in the research octane number of petroleum fuels - Rohmah Insyirah Handayani; Bambang Murdaka Eka Jati; Eko Sulistya (Journal of Physics: Theories and Applications, 2026)
The Research Octane Number (RON) is a key quality parameter of gasoline that reflects the molecular structural characteristics of hydrocarbons; however, its conventional determination relies on standardized engine testing, which is impractical for rapid laboratory analysis. This study aims to analyze the characteristics of 1H NMR spectra of gasoline with different RON values and to evaluate the potential of alternative approaches based on electromagnetic induction and capacitive methods as discriminative parameters for RON. The methodology includes 1H NMR spectral analysis using region-based integration of chemical shifts without individual compound identification, as well as evaluation of the response of mutual induction systems and RC and RLC capacitive circuits to various gasoline samples. The results show that 1H NMR spectra exhibit clear differences in the distribution of aliphatic and aromatic signals among gasoline samples with different RON values, whereas the electromagnetic induction system does not demonstrate sufficient sensitivity due to the non-magnetic nature of gasoline. The capacitive approach is capable of detecting media with large permittivity contrast but is not yet sufficiently sensitive to discriminate subtle variations among gasoline samples. This study provides a methodological basis for the application of 1H NMR in the molecular structural characterization of gasoline and a critical evaluation of the limitations of sensor-based approaches relying on electromagnetic responses.